The Fragile Archive: A Case Study on the Digital Loss and Partial Recovery of Indonesia’s Early Digital Poetry Anthology - Mohammad Rokib; Mirian Ngozi Alike; Moh. Mudzakkir; Parmin; Lutfiyah Alindah (Record and Library Journal, 2026)
Background of the study: The emergence of digital literature has transformed the production of literary works, while simultaneously foregrounding archiving as a critical concern, given that such works depend on technologies that are prone to potential loss. Purpose: The study examines the transition challenge of digital material fragility focusing on CD-ROM of APDC as a case in a developing nation, revealing similar preservation risks in global context. Method: Using a critical case study design, the study traces the process of recovering APDC materials. The data collection involved archival analysis, file retrieval through legacy hardware, and metadata. It also employs an interpretive perspective to examine the wider socio-technical factors. Findings: The result indicate that only five poems, out of a total of 169 composed by 55 authors, could be retrieved from a single surviving CD-ROM. This limited regeneration points to the extreme vulnerability of early digital literary works, along with the absence of dependable preservation systems. Conclusion: The inaccessibility of born-digital literature is not merely a technical issue, but a systemic failure of archival practices that places cultural memory at risk.